(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2020)
The first stage of modern societies was defined in one part of the world by the establishment of a direct link between the sacred world and the human world: this is monotheism. In other parts, early stages were defined by empires or by categories of purity, such as castes in India. In the western world, as well as in places like Japan, a second stage links sacredness and political power, for which the paradigmatic political institutions were absolute monarchies. The third stage is what we call industrial society, which is defined by a massive increase in labor productivity, mechanization and class struggle at the social level. Now we are entering in a new “society of communication” which is no longer based neither on production nor on nation-states and cities, but rather on global systems. In this new type of society, the social actors must be “total”, that is they must be active in the cultural – mediatic – domain as well as in the political and economic fields. While in industrial societies the main actors were generally considered to be social classes, and the central notions were production and class conflict, in societies of communication the main actors represent more total categories, as those of “women” or “migrants” do in western countries today, and the central notion is subjectivation, which language is that of fundamental human rights.